Identification of HIR, EDS1 and PAD4 Genes Reveals Differences between Coffea Species That May Impact Disease Resistance - Sílvia Tavares; Helena Azinheira; Javier Valverde; A. Jesus Muñoz-Pajares; Pedro Talhinhas; Maria do Céu Silva (Agronomy, 2023)
Coffee, a widely consumed important agricultural product, is mainly produced from two species, Coffea arabica (Arabica coffee) and C. canephora (Robusta coffee). Timor Hybrid (HDT) is a population resulting from a natural cross between C. arabica and C. canephora. HDT derivatives have a high spectrum of resistance to different races of Hemileia vastatrix (Hv), the causal agent of coffee leaf rust. A RNAseq database, obtained from HDT832/2 leaves inoculated with Hv (Host Resistance) and Uromyces vignae (Uv, Nonhost Resistance), showed the presence of genes implicated in the hypersensitive response and salicylic acid pathway. Hypersensitive Induced Reaction (HIR) gene family, Enhanced Disease Susceptibility1 gene (EDS1), and Phytoalexin Deficient 4 (PAD4) gene are involved in host and nonhost resistance. Relative expression calculated by RT-qPCR was used to confirm and expand the transcriptome analysis. HDTHIR4, HDTEDS1, and HDTPAD4 showed the highest upregulation in response to Hv and Uv inoculation, confirming a similar trend in host and nonhost resistance in HDT. HIR and EDS1/PAD4 gene families were characterized for the first time in the three available Coffea genomes. HIR genes were quite conserved between Coffea species. Surprisingly, EDS1 and PAD4 genes revealed major differences in gene structure. The PAD4 predicted protein from C. arabica does not include both conserved domains of the EDS1/PAD4 family, and the EDS1 putative protein from C. canephora includes a formin domain unusual in the same protein family. The variability shown by EDS1/PAD4 gene family may impact the disease resistance response of Coffea species, which can be surveyed for the gene sequences that will produce a more resistant phenotype.